2002
DOI: 10.1038/415150a
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-based magnetic refrigerants for room-temperature applications

Abstract: Magnetic refrigeration techniques based on the magnetocaloric effect (MCE) have recently been demonstrated as a promising alternative to conventional vapour-cycle refrigeration. In a material displaying the MCE, the alignment of randomly oriented magnetic moments by an external magnetic field results in heating. This heat can then be removed from the MCE material to the ambient atmosphere by heat transfer. If the magnetic field is subsequently turned off, the magnetic moments randomize again, which leads to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

33
1,282
2
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,524 publications
(1,329 citation statements)
references
References 10 publications
33
1,282
2
12
Order By: Relevance
“…Contrary to the old belief that such effects, while common, are miniscule, a large variety of giant caloric effects has been recently discovered in some ferroic materials [1][2][3][4][5][6][7][8][9][10] . These discoveries have opened the door to the use of these giant effects in an efficient and environmentally friendly solid-state refrigeration technology.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Contrary to the old belief that such effects, while common, are miniscule, a large variety of giant caloric effects has been recently discovered in some ferroic materials [1][2][3][4][5][6][7][8][9][10] . These discoveries have opened the door to the use of these giant effects in an efficient and environmentally friendly solid-state refrigeration technology.…”
mentioning
confidence: 91%
“…Moreover, given a relative abundance of extrinsic multiferroics among ferroics with multiple order parameters, such prediction may open an unusual route to solid state refrigeration advancement. Recent discoveries of giant caloric effects in some ferroic materials [1][2][3][4][5][6][7][8][9][10] have opened the door to the use of solidstate materials as an alternative to gases for conventional and cryogenic refrigeration 11 . The wide class of ferroics includes such diverse materials as ferromagnets and magnetic materials, ferroelectrics, ferroelastics and multiferroics.…”
mentioning
confidence: 99%
“…These magnetoelastic transitions have been utilized in the intensive investigations of a large body of giant magnetocaloric materials [19][20][21][22][23][24][25][26][27] . In contrast, in typical FMMTs, the change of structural symmetries of austenite and martensite is remarkable [6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…Along with the Arrott plots, very interesting could be a comparison of magnetic entropy change curves. In the high magnetic field of 5 T, the highest entropy change was evaluated for the Mn 1 was even lower i.e. 14 J/(kg·K) at the same magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…Interesting properties of MnFe(P 1 − x Y x ) compounds were for the first time reported by Tegus et al [1] in MnFeP 0.45 As 0.55 . In their other paper, the authors have shown an impact of changing P/As ratio on the Curie temperature and magnetic entropy change [2].…”
Section: Introductionmentioning
confidence: 89%